Beyond Lp Norms: Delving Deeper Into Robustness to Physical Image Transformations - Sehwag, Vikash; Stokes, Jay; Zhang, Cha (Military Communications Conference, 2021)
With the increasing adoption of deep learning in computer vision-based applications, it becomes critical to achieve robustness to real-world image transformations, such as geometric, photometric, and weather changes, even in the presence of an adversary.